Do insomnia and/or sleep disturbances predict the onset, relapse or worsening of depression in community and clinical samples of children and youth? Protocol for a systematic review and meta-analysis - Sarah Bonato; Peter Szatmari; John D Haltigan; Cecilia Marino; Brendan Andrade; Madison Aitken (BMJ Open)
Introduction Disturbed sleep represents a potentially important modifiable risk factor for the development of depression in children and youth. This protocol for a systematic review proposes to investigate whether insomnia and/or sleep disturbances predict child and youth depression in community and clinical-based samples.Methods and analysis The protocol adheres to the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols guidelines. English-written, longitudinal studies that quantitatively estimated the prediction of depression by insomnia and/or sleep disturbances in individuals 5–24 years of age will be included. EMBASE, MEDLINE, PsychINFO, Scopus and Web of Science and grey literature will be searched from 1980 to the present. For the selection of studies, two reviewers will be involved. Data extraction will be conducted by one author and checked independently by a second author. Risk of bias will be appraised using the Research Triangle Institute Item Bank tool. Heterogeneity will be measured using the I2 statistics. Meta-analysis will be carried out if ≥3 results are available and if outcome measures can be pooled. The choice between a random-effect or fixed-effect model will be based both on the I2 statistics and the participant and study characteristics of the combined studies. Results of the meta-analyses will be summarised by a forest plot. Analyses will be performed in subgroups stratified by key variables defined depending on the amount and type of information retrieved.A narrative synthesis will be conducted in place of the meta-analysis should the pooling of data not be possible. Quality of evidence will be rated using the Grading of Recommendations Assessment, Development and Evaluation guidelines.As this is a protocol for systematic review and meta-analysis of published data, ethics review and approval are not required. The findings will be published in a peer-reviewed journal and disseminated at scientific conferences and in patient advocacy organisations.PROSPERO registration number CRD42019136729.